2021
DOI: 10.3390/foods10092118
|View full text |Cite
|
Sign up to set email alerts
|

Development of Optimal Digesting Conditions for Microplastic Analysis in Dried Seaweed Gracilaria fisheri

Abstract: Currently, research on the accumulation of microplastics (MPs) in the marine food web is being highlighted. An accurate and reliable digestion method to extract and isolate MPs from complex food matrices has seldom been validated. This study aimed to compare the efficacy of MP isolation among enzymatic-, oxidative-, and the combination of two digestion methods on red seaweed, Gracilaria fisheri. The dried seaweed sample was digested using three different methods under various conditions using enzymes (cellulas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 60 publications
(106 reference statements)
0
4
0
Order By: Relevance
“…DE). However, only two studies [10,58] reported achieved the digestion efficiency necessary. In the case of meat samples, only one study by Habib et al (2022) [32] proposed an analytical approach, but the effects of combining KOH with high temperature (i.e., 75 • C) have not been investigated.…”
Section: Analytical Challenges In Microplastic's Determination In Foo...mentioning
confidence: 99%
See 2 more Smart Citations
“…DE). However, only two studies [10,58] reported achieved the digestion efficiency necessary. In the case of meat samples, only one study by Habib et al (2022) [32] proposed an analytical approach, but the effects of combining KOH with high temperature (i.e., 75 • C) have not been investigated.…”
Section: Analytical Challenges In Microplastic's Determination In Foo...mentioning
confidence: 99%
“…However, due to the size limitations of the techniques, the qualification of smaller microplastics (<20 µm) using µ-FTIR should be reassessed (see Section 4). µ-FTIR >20 µm 0.39-7.02 mm PE, PP [20] µ-ATR-FTIR >7 µm 65-2500 µm LDPE, HDPE [21] µ-ATR-FTIR >7 µm 300-5000 µm PP, PE, PET, PS [22] µ-Raman >0.45 µm 5 to >1000 µm Rayon, PP, PES, PE [23] µ-ATR-FTIR >7 µm 23.2 µm-3.9 mm PA, PU [24] µ-FTIR >20 µm 45-100 µm HDPE, PP, PET, PS, PA [25] µ-FTIR >20 µm 3.8 µm-5.2 mm CP, PS, PA, PAR [26] SEM-EDX N/A 100-500 µm PE [27] µ-FTIR >20 µm 30 µm-3.5 mm PET, PP, PE [28] µ-FTIR >20 µm N/A PET [29] µ-FTIR >20 µm <300 µm PVC, PET, PTFE, HDPE, Nylon, ABS [30] µ-FTIR >20 µm 15.6-1151.1 µm PE [32] µ-FTIR >20 µm 5-20 µm PS, PP, PE [34] µ-Raman >0.45 µm <5 µm PET [35] µ-ATR-FTIR >7 µm N/A PES, PET, PS [42] µ-Raman >0.45 µm 1.2-10 µm PE, PET, PC [43] µ-FTIR >20 µm 0.06-0.11 mm PE, PP, PS, Nylon [44] µ-FTIR >20 µm 0.2-22 mm PE, PP [46] µ-Raman >0.45 µm 15-1175 µm PS [47] SEM/EDX N/A 100-1000 µm PET, PE [50] µ-Raman >0.45 µm <300 µm PE, PP, PET [54] µ-FTIR >20 µm 520 nm-270 µm Nylon, PET [56] µ-FTIR >20 µm 453-3885 µm Nylon, PP, HDPE [60] µ-Raman >0.45 µm N/A PE, PP, PS, PVC, PET [58] µ-Raman >0.45 µm 0.1-3 mm PA, PET, PAS [63] µ-ATR-FTIR >7 µm 24-1670 µm PES, ABS, EPM, nylon-6, CP, and viscose [51] µ-FTIR >20 µm <100 µm to 5000 µm PP, PE [52] µ-FTIR >20 µm 50-500 µm PVC, LDPE, PS, PP [57] µ-FTIR >20 µm 20-150 µm PE, PP, PS [61] µ-Raman >0.45 µm Abbreviations: Polyolefin, PO; Ethylene-propylene copolymer, EPM.…”
Section: Microplastic's Qualification: Techniques' Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prihandari et al [ 105 ] optimized a method for digesting MPs to analyze MPs in dried Gracilaria fisheri seaweed. The authors employed digestive methods, such as cellulase-based enzymatic and H 2 O 2 -based oxidative methods, and a combination of enzymatic and oxidative digestion methods for the analysis of MPs from the dried samples of edible red seaweed, Gracilaria fisheri .…”
Section: Comprehensive Overview Of Mp Impacts On Edible Marine and Fr...mentioning
confidence: 99%